Pengaruh Perencanaan Pajak, Mekanisme Bonus, dan Kepemilikan Asing terhadap Transfer Pricing - Humiras Hutabarat; Kenny Ardillah (UNIVERSITAS KALBIS, 2022)
Transfer pricing is the result of today's business growth. National companies are now becoming multinational companies whose activities are not only concentrated in one country, but in several countries. This is done for tax avoidance in order to obtain high profits. The purpose of this study is to determine the effect of tax planning, bonus mechanism and foreign ownership on transfer pricing. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2017. The total sample selected by purposive sampling technique is 100 companies. This study uses the classical assumption test, model feasibility test, multiple linear regression analysis and hypothesis testing with the Eviews 10 data processing application. The results of this study indicate that tax planning has no significant effect on transfer pricing, the bonus mechanism has no significant effect on transfer pricing and foreign ownership. positive and significant effect on transfer pricing.